Morbidity of the child population with mental disorders and behavioral disorders in the Russian Federation in 2018 and 2022 - V. V. Freize; M. V. Anokhina; L. V. Malyshko; A. Yu. Goncharenko; N. V. Semenova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In recent years, there have been significant negative changes in health and, as a consequence, an increase in medical and social problems among the population of children and adolescents. One of the factors that have a negative impact on these processes is the presence of mental disorders, which can be caused by various reasons, including biological ones, including metabolic disorders. The article presents the results of a comparative analysis of the indicators of general and primary morbidity of mental disorders and behavioral disorders in children and adolescents in the Russian Federation as a whole for 2018 and 2022, obtained from the relevant forms of federal statistical observation No. 10 “Information on diseases with mental disorders and behavioral disorders (except for diseases related to substance use)”. The analysis included data on the number of child and adolescent population in the Russian Federation in 2018 and 2022, obtained from the reporting forms of the federal state statistics service.The presented results make it possible to assess the dynamics of the prevalence of mental disorders in groups of children and adolescents, which can contribute to the improvement of programs and measures for their prevention and treatment, as well as to determine the needs for medical care of minors in the Russian Federation and identify factors that increase the risk of developing certain diseases.